Enseñanza del Derecho: Participación de las mujeres y enfoque de género en 100 años de la Facultad de Derecho la Pontificia Universidad Católica del Perú - Huaita Alegre, Marcela (2019)
Abstract: The gender perspective applied to the Law is one of the major transformations that this discipline has experienced in recent decades. For this reason, in the centenary of the Faculty of Law of the Catholic University of Peru (PUCP), one of the oldest academic units of this prominent Peruvian university, this article will review how gender studies began in this faculty in the 1990s. Taking into account the Latin American process, several decades will be reviewed, identifying historical periods in the incorporation of the gender perspective in the teaching of law in Peru. From there, it will be discussed how gender and law studies have occupied an important space within curricular contents, until they even question the teaching process itself. Likewise, the barriers and difficulties that women have faced to make their way into a Faculty where they are currently a majority will be quickly discussed. After reviewing this process, some reflections will be proposed on the challenges and opportunities that the teaching of Law with a gender focus faces towards the new centenary.\n